2014
DOI: 10.5455/2320-1770.ijrcog20141224
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic pain in women: comparative study between ultrasonography and laparoscopy as diagnostic tool

Abstract: Background: Chronic pelvic pain is a major cause of morbidity among the reproductive age group women. The study on patients of chronic pelvic pain aimed to compare the diagnostic accuracy of ultrasonography and laparoscopy in these patients Methods: The study was conducted on 100 patients of chronic pelvic pain attending the gynaecology outdoor and were subjected to thorough clinical examination followed by ultrasonography and laparoscopic examination. Results: Maximum number of cases of chronic pelvic pain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Baloch S et al in their study found 90.6% patients were married and 47.1% were nulliparous. 18 In present study, maximum patients (59.79%) presented with abdominal tenderness which was similar to that found by study of Rawat et al 17 The other clinical features were adnexal tenderness, adnexal mass and restricted mobility which were almost similar to that found by Rawat et al 17 The incidence of adhesions, ovarian cyst, fibroid, endometriosis and pelvic congestion syndrome is correlating with that found in study done by Jyotsana L et al 19 The incidence of patients with normal findings on laparoscopy was similar to that found in study conducted by Kamilya et al and Jyotsana L et al 19,20 In present study, maximum number of patients were diagnosed to have normal findings (22.68%) on laparoscopy followed by adhesions (17.58%) and PID (14.43%). Whereas in study conducted by Kamilya et al and Jyotsana L et al, the maximum number of patients diagnosed were of PID followed by normal findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Baloch S et al in their study found 90.6% patients were married and 47.1% were nulliparous. 18 In present study, maximum patients (59.79%) presented with abdominal tenderness which was similar to that found by study of Rawat et al 17 The other clinical features were adnexal tenderness, adnexal mass and restricted mobility which were almost similar to that found by Rawat et al 17 The incidence of adhesions, ovarian cyst, fibroid, endometriosis and pelvic congestion syndrome is correlating with that found in study done by Jyotsana L et al 19 The incidence of patients with normal findings on laparoscopy was similar to that found in study conducted by Kamilya et al and Jyotsana L et al 19,20 In present study, maximum number of patients were diagnosed to have normal findings (22.68%) on laparoscopy followed by adhesions (17.58%) and PID (14.43%). Whereas in study conducted by Kamilya et al and Jyotsana L et al, the maximum number of patients diagnosed were of PID followed by normal findings.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, maximum patients (36.08%) belonged to age group 20-30 years. Rawat et al 17 did a study and found maximum patients (37%) belonged to age group 25-30 years age group. Baloch S et al found 62.4% patients in age group 26-35 years.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chronic PID was found in majority (47%) of the cases evidenced by presence of regularly enlarged uterus with tubo-ovarian masses, hydro-salpinx, tortuous tubes or fluid in pouch of Douglas as well as presence of congested adnexa. [13] With above explanation, Vikaraprikriti and Adhisthanantarani are compiled as…”
Section: Diagnostic Testingmentioning
confidence: 99%